2020
DOI: 10.3390/ijerph17197023
|View full text |Cite
|
Sign up to set email alerts
|

Canan Outdoor Multisurface Terrain Enhance the Effects of Fall Prevention Exercise in Older Adults? A Randomized Controlled Trial

Abstract: Walking on complex surface conditions in outdoor environments is important for active aging. This study aimed at examining whether fall prevention exercise integrated with an outdoor multisurface terrain compared with indoor solid ground was more beneficial for older adults. Twenty-two older nursing home residents were randomly assigned to outdoor multisurface terrain (n = 11, 79.5 ± 2.1 years) or indoor solid ground (n = 11, 78.8 ± 5.2 years) groups. Training occurred five times per week (30 min) for 3 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 35 publications
(53 reference statements)
0
15
0
5
Order By: Relevance
“…35 The complex relationship between fear of falling, balance confidence, and balance performance may also have influenced our results. 32 Because it has been shown that a fall prevention program integrated with an outdoor multisurface terrain has improved balance, gait, and mobility measures in older adults when compared with indoor solid ground 36 and those preliminary outcomes of a feasibility study have shown a reduction of outdoor falls among older adults, 37 future fall prevention trials including people with PD should investigate whether an outdoor multimodal training and the adoption of fall protective behavior 38 would reduce the number of injurious falls in this population.…”
Section: Discussionmentioning
confidence: 99%
“…35 The complex relationship between fear of falling, balance confidence, and balance performance may also have influenced our results. 32 Because it has been shown that a fall prevention program integrated with an outdoor multisurface terrain has improved balance, gait, and mobility measures in older adults when compared with indoor solid ground 36 and those preliminary outcomes of a feasibility study have shown a reduction of outdoor falls among older adults, 37 future fall prevention trials including people with PD should investigate whether an outdoor multimodal training and the adoption of fall protective behavior 38 would reduce the number of injurious falls in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of included studies are presented in Supplementary Table S3. Six of the ten included trials were parallel-group randomized controlled trials [18,20,[27][28][29][30][31][32], whereas three studies were parallel-group controlled trials with no reporting of randomization [19,33,34]. One study was a cluster-randomized, counterbalanced crossover trial [17].…”
Section: Trial Design Characteristicsmentioning
confidence: 99%
“…All studies aimed to compare the effect of outdoor exercise versus indoor exercise on psychological, physical, and/or behavioural outcomes. Two of these studies focused on specific environmental variables: cold exposure (outdoors at −5 [19] and terrain (outdoor multisurface path versus indoor solid floor) [20]. Three of the studies also investigated additional independent variables (i.e., vitamin D supplementation [29] and exercise [18,32]) by including additional intervention groups or control groups [18,29,32] that were not relevant to this review and will not be further discussed.…”
Section: Trial Design Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, these exercises resulted in improved physical functions such as mobility, strength, balance, and gait. 14 , 15 , 16 , 17 , 18 ) Literature reports also indicated that the prevalence of LS was higher in patients with RA than in the general population. 19 , 20 , 21 ) We believe that the locomotion training recommended by the JOA (Locotre), unlike aerobic exercise and general resistance exercise, is low-intensity training that can be safely performed at home by RA patients.…”
Section: Introductionmentioning
confidence: 96%